EFFECTIVENESS OF DIGITAL HEALTH EDUCATION PLATFORMS IN ENHANCING PHYSICAL FITNESS AWARENESS IN ENUGU STATE SCHOOLS (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Educational platforms Digital health education platforms have become new tools to be used to create health awareness, especially in the educational sphere. The research paper will determine how effective these platforms are in promoting awareness of physical fitness among the secondary school students in Enugu State, Nigeria. Surveys, interviews, and fitness awareness tests were used to collect data on 1,200 students and 60 teachers in 12 schools through a mixed-methods approach. The results reveal that digital platforms are very effective in enhancing students knowledge on physical fitness concept as 32% of the students knowledge awareness scores increased after the intervention. Nevertheless, there are barriers like insufficient internet connectivity and poor training of teachers that interfere with the best implementation. The paper emphasizes the possibility of digital tools in filling gaps in the conventional domain of health education together with outlining the contextual impediments that should be considered in the policies. Infrastructure investment, capacity building of the teachers, to maintain the effect of digital health education are recommendable.